ETIKA KEPEMIMPINAN DALAM PERSPEKTIF ISLAM DAN KORELASINYA TERHADAP KINERJA - Zaedun Na'im (Evaluasi: Jurnal Manajemen Pendidikan Islam, 2022)
This paper aims to examine more deeply about leadership ethics in the view of Islam and the relationship between leadership ethics and the performance of employees or those they lead. This is an interesting study to discuss considering that in an organization that is the center of attention and its policies are awaited in an organization is the figure of a leader, so that in a leader an ethics is needed, because a leader becomes uswah or an example to his subordinates and that have a significant influence on the performance of their subordinates. In this study, this type of research uses qualitative research with a library research approach or library study with data collection techniques through various references, then data reduction and conclusions are carried out. The results showed that. Leadership ethics in the view of Islam as exemplified by the Prophet with his leadership traits, namely al sidq, amanah, fathonah and tablig and there is a relationship between ethical leadership and ethical performance on the influence of employee performance, this is because the influence of ethical leadership can be realized good performance ethics so that the collaboration between ethical leadership and work ethics has a positive impact on optimizing employee performance